A Durable and Efficient Electrocatalyst for Saline Water Splitting with Current Density Exceeding 2000 mA cm−2. (12th March 2021) - Yang, Fengning; Luo, Yuting; Yu, Qiangmin; Zhang, Zhiyuan; Zhang, Shuo; Liu, Zhibo; Ren, Wencai; Cheng, Hui‐Ming; Li, Jiong; Liu, Bilu
Abstract: Water electrolysis is promising for industrial hydrogen production to achieve a sustainable and green hydrogen economy, but the high cost of the technology limits its market share. Developing efficient yet economic electrocatalysts is crucial to decrease the cost of electricity and electrolytic cell. Meanwhile, electrolysis in seawater electrolyte can further reduce feedstock cost. Here, a type of electrocatalyst is synthesized, where trace precious metals are strongly anchored on a corrosion‐resistive matrix. As an example, the produced Pt/Ni‐Mo electrocatalyst only needs an overpotential of 113 mV to reach an ultrahigh current density of 2000 mA cm −2 in the saline‐alkaline electrolyte, demonstrating the best performance reported thus far. It shows high activity and long durability in various electrolytes and under harsh conditions, including strong alkaline and simulated seawater electrolytes, and under elevated temperatures up to 80 ° C. This electrocatalyst is produced on a large scale at a low cost and shows good performance in a commercial membrane electrode assembly stack, demonstrating its feasibility for practical water electrolysis. Abstract : Developing efficient yet economic electrocatalysts for saline water splitting is crucial to achieve a sustainable and green hydrogen economy. Here, a Pt/Ni‐Mo electrocatalyst is synthesized, where highly dispersed Pt nanoparticles are anchored on a corrosion‐resistive matrix. It needs an overpotential of 113 mV to reach 2000 mA cm −2 in the saline‐alkaline electrolyte and shows good stability under harsh practical conditions.